Spatiotemporal dynamics of the 2025–26 measles resurgence in Mexico: A national scan‑statistic analysis - Oliver Mendoza-Cano; Xóchitl Trujillo; Mónica Ríos-Silva; Jaime Alberto Bricio-Barrios; Agustin Lugo-Radillo; Rosa Tapia-Vargas; Jesús Venegas-Ramírez; Eder Fernando Ríos-Bracamontes; Herguin Benjamin Cuevas-Arellano; Yolitzy Cárdenas; Raúl Aquino-Santos; Iris Anecxi Jiménez-Vieyra; et al. (PLoS ONE, 2026)
Background Following over two decades of eliminated endemic transmission, Mexico experienced a significant measles resurgence in 2025–26. Declining vaccine coverage and pandemic-related service disruptions created subnational immunity gaps. We aimed to characterize the spatiotemporal patterns of this outbreak to identify areas of sustained transmission. Methods We conducted a retrospective surveillance study of all confirmed measles cases reported nationally over a 50-week period (mid-February 2025 to February 10, 2026). Using municipal-level data and population projections, we applied Kulldorff’s space–time scan statistic (discrete Poisson model) to identify statistically significant clusters where incidence exceeded population-based expectations. Results A total of 8,205 confirmed cases were reported across 337 municipalities during the study period. Overall, 23 space–time clusters were identified, of which 19 were statistically significant ( p < 0.001). The primary cluster, located in northern Mexico between epidemiological weeks 6 and 30, represented the focus of transmission, encompassing 89 municipalities and 4,012 cases (relative risk [RR] = 103.7). Secondary clusters reflected additional transmission patterns, including a large late-phase cluster in western Mexico with 1,493 cases (RR = 31.5), as well as several smaller, short-duration micro-outbreaks with markedly elevated localized risk (RR > 200). Conclusions The resurgence of measles was characterized by marked subnational heterogeneity, with both sustained regional transmission and localized surges. A late-stage, low-intensity cluster spanning 244 municipalities suggested a transition toward more diffuse national transmission. These spatiotemporal patterns suggest that geographically differentiated approaches, including subnational surveillance and targeted “mop-up” immunization campaigns, may be needed to address immunity gaps and support efforts toward restoring Mexico’s elimination status.